DISPENSASI PERNIKAHAN DALAM PRESPEKTIF HUKUM POSITIF DI INDONESIA - Kusumawardana, Haris; Hariadi, Wahyu; Iskatrinah, Iskatrinah (Universitas Wijayakusuma Purwokerto, 2025)
According to the Explanation of Article 7 paragraph (2) of the Marriage Age Change Law, what is meant by